The impact of bile acid supplementation in the diet of post-larval shrimp: Growth performance, lipid metabolism, gut microbiota, and molecular responses - Mrope Peter; Yucheng Liu; Yohana Mpwaga Alatwinusa; Hongyu Liu; Junming Deng; Beiping Tan; Shiwei Xie (Aquaculture Reports)
This study aimed to evaluate the impact of dietary supplementation of bile acids (BAs) on the growth performance, antioxidant, lipid metabolism, immunity, gut microbiota, and molecular responses of Litopenaeus vannamei post-larvae (initial weight 1.30 ± 0.00 mg) were assigned to four dietary treatments containing different levels of dietary Bile acid (BA), (B0 =0.00, B1 =0.02, B2 =0.04, and B3 =0.08 %), with each diet distributed to quadruplicate groups of 40 shrimp per tank. BA inclusion increased final body weight, weight gain rate (WGR), and specific growth rate (SGR) compared to the control group (B0). Antioxidant indicators, such as superoxide dismutase (SOD) and total antioxidant capacity (T-AOC), exhibited an increase with elevated BA levels, whereas malondialdehyde (MDA) content showed a decrease. Analysis of hepatocytes demonstrated a notable upregulation of genes associated with lipid metabolism, specifically srebp, ampk, cpt-1, and baat. The expression of immune-related genes, including toll, Relish, and myd88, was significantly upregulated following BA supplementation (P < 0.05). Simultaneously, growth-related genes (4ebp, raptor, tor) were significantly upregulated in groups supplemented with BA (P < 0.05). Dietary BA supplementation enhanced gut microbiota diversity and richness of Bacteroidetes and Firmicutes observed in diets supplemented with BA. Finally, these findings together indicate that the inclusion of 0.08 % BA in post-larval shrimp diets ideally enhances development, strengthens antioxidant and immunological responses, regulates lipid metabolism, and promotes a healthy gut flora. These results highlight the promise of BAs as novel bioactive additions for the formulation of advanced, efficient aquafeed.